Simultaneous consumption of drugs and their implications on cognitive functioning - Hugo Sánchez Castillo; Rodrigo Iván Castañeda Garrido; Diana Berenice Paz Trejo; Daniel Soltero de la Rosa; Pável Zárate González (Centros de Integración Juvenil A.C., 2018)
Introduction: drug abuse is a health problem that affects millions of people around the world. It could be defined as a concurrent condition in which the behavior has the goal of produce a pleasant sensation and reduce the discomfort produced by the interruption of the drug administration. The drug retirement produces cognitive alterations, particularly in memory and executive function. Those effects are due to the vulnerability of prefrontal cortex to the drug effects. Poly drug use is defined as the simultaneous intake, or separated in short time lapses, of several drugs. This kind of drug intake has been poorly studied in comparison to other addictions. Objective: to evaluate the effects of poly drug use in three groups of drug consumers evaluated with a neuropsychological battery. Method: thirty-six poly drug consumers were included and eleven non consumers integrated a control group (total sample: 47 subjects). Poly drug consumers were divided in three different groups depending on the kind of drugs consumed. All poly drug users were evaluated with the Neuropsychological battery "Neuropsi Atención y Memoria" and were compared against the performance of control group. Conclusion and discussion: neuropsychological affections were observed, particularly in verbal memory and evocation (both verbal and visuospatial) as well as in abstract attitude and inhibition (p < 0.05). We observed several relapses and readmissions in the rehabilitation center. The findings over inhibition and abstract attitude could explain the poor adhesion to treatment, alterations in everyday life and several relapses.